2006
DOI: 10.1103/physrevlett.96.028107
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organized Criticality Model for Brain Plasticity

Abstract: Networks of living neurons exhibit an avalanche mode of activity, experimentally found in organotypic cultures. Here we present a model that is based on self-organized criticality and takes into account brain plasticity, which is able to reproduce the spectrum of electroencephalograms (EEG). The model consists of an electrical network with threshold firing and activity-dependent synapse strengths. The system exhibits an avalanche activity in a power-law distribution. The analysis of the power spectra of the el… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
203
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 245 publications
(222 citation statements)
references
References 40 publications
16
203
1
1
Order By: Relevance
“…In a random network of size N with connectivity probability c, the critical parameter α is approximately equal to α cr N /c, where α cr N is obtained from the critical parameter region of the fully connected network of size c × N. If the connections in a partially connected random network are not chosen independently (for example, 'small-world' connectivity 18 ), even more accurate power laws than for the independent case with the same average connectivity are found. A similar phenomenon occurs in the grid network 19 which has been used to model criticality in electroencephalograph recordings.…”
Section: (4)mentioning
confidence: 99%
“…In a random network of size N with connectivity probability c, the critical parameter α is approximately equal to α cr N /c, where α cr N is obtained from the critical parameter region of the fully connected network of size c × N. If the connections in a partially connected random network are not chosen independently (for example, 'small-world' connectivity 18 ), even more accurate power laws than for the independent case with the same average connectivity are found. A similar phenomenon occurs in the grid network 19 which has been used to model criticality in electroencephalograph recordings.…”
Section: (4)mentioning
confidence: 99%
“…Indeed, the finding of scale invariance does not exclude long-range or short-range heterogeneous corticocortical projections. Numerical simulations have shown that neuronal avalanches can arise at the critical state in models with scale-free (26), fully connected (27), random (28), and nearest-neighbor (18,26) topologies, although in each case the conditions to reach criticality can be different. In cortical cultures, the neuronal avalanches establish a functional small-world architecture with specific and highly diverse point-topoint connectivity between cortical sites that is, the network representing these site activations is densely interconnected, globally as well as locally (29).…”
Section: Scale Invariance In Time Nlfp Amplitude and Finite-size Scmentioning
confidence: 99%
“…Candidate mechanisms for leading the network into this state include competitive activity-dependent attachment and pruning (e.g. Bornholdt & Rohlf 2000;de Arcangelis et al 2006), short-term synaptic plasticity (Levina et al 2005) or some combination of homeostatic regulation of excitability and Hebbian learning (Hsu & Beggs 2006).…”
Section: Modelsmentioning
confidence: 99%